The formation of moral consciousness of future teachers in terms of professional education - O. V. Solovieva; E. P. Shmatova (Вестник Северо-Кавказского федерального университета)
The article presents the results of a moral self-awareness study involving future teachers. There is a view on the level of the cognitive, emotional, and behavioral components of moral self-awareness among 1st and 4th year students majoring in various areas. The item also provides a focus on the interrelation between the selfreference indicators and the components of students’ self-awareness. The author provides a description of the system for psychological assistance to moral self-awareness development in those training to become teachers